Theoretical And Practical Gaps In Policy Making Process In Five Organizations - Nor Ashikin Mohamed Yusof; Sri Widias Asnam; Aini Suzila Anas; Nur Suraya Mustapha; Natrah Emran; Nor Azalina Azman (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2019)
Policy making is an integral part of policy studies. Theoretically the process of developing a policy document is neither easy nor simple. Far from merely copying the policy provisions of other countries, the process of developing a policy document must go through specific steps and procedures commonly known as policy cycle with each cycle serves specific functions. Although bench-making study is highly encouraged, it is also preferable for policymakers to align the policy making exercise in accordance to proven theory, model, method and process. Not many know about all these processes and steps. Some very senior and seasoned policymakers even think that there is no need for them to learn and pursue knowledge in policymaking simply because they have long years of practical experiences in developing, formulating, implementing, enforcing and subsequently analyzing and evaluating policies. This article reports case studies involving five national policy documents and internal policies at several key governmental department and organizations. The findings from the study enables the researchers to make a comparison between the theory of policy making and the practice of policy making in Malaysia. The findings show that there is still a huge gap between theory and practice in policymaking and policy studies in Malaysia. There are instances where few policy makers or top management personnel choose not to follow or ignorant about the steps of policy cycles. Although policy studies might have a very bright future in Malaysia but the journey in educating relevant parties would be a long one beginning with a correct perception and willingness to change attitudes. Keywords; policy studies, policy cycle, policy making process